Do Humans Really Prefer Semi-open Natural Landscapes? A Cross-Cultural Reappraisal - Hägerhäll, Caroline M.; Ode Sang, Åsa; Englund, Jan-Eric; Ahlner, Felix; Rybka, Konrad; Huber, Juliette; Burenhult, Niclas (Frontiers in Psychology, 2018)
There is an assumption in current landscape preference theory of universal consensus in human preferences for moderate to high openness in a natural landscape. This premise is largely based on empirical studies of urban Western populations. Here we examine for the first time landscape preference across a number of geographically, ecologically and culturally diverse indigenous populations. Included in the study were two urban Western samples of university students (from southern Sweden) and five non-Western, indigenous and primarily rural communities: Jahai (Malay Peninsula), Lokono (Suriname), Makalero (Timor), Makasae (Timor), and Wayuu (Colombia). Preference judgements were obtained using pairwise forced choice assessments of digital visualisations of a natural landscape varied systematically on three different levels of topography and vegetation density. The results show differences between the Western and non-Western samples, with interaction effects between topography and vegetation being present for the two Swedish student samples but not for the other five samples. The theoretical claim of human preferences for half-open landscapes was only significantly confirmed for the student sample comprising landscape architects. The five non Western indigenous groups all preferred the highest level of vegetation density. Results show there are internal similarities between the two Western samples on the one hand, and between the five non-Western samples on the other. To some extent this supports the idea of consensus in preference, not universally but within those categories respectively.